Child safety reporting, services, and child welfare interventions with newcomer families during the COVID-19 pandemic: A survey of ontario child welfare workers. - Daniel Kikulwe; Derrick Ssewanyana; Sarah Maiter (Child Protection and Practice, 2024)
Background: Newcomer families with child welfare involvement face complex COVID-19 related challenges that are still less understood within the Canadian context. Objective: This study explored views on the changes in child safety reporting and interventions with newcomer families during the COVID-19 pandemic. Participants: and Setting: Participants were 63 child welfare workers from Children's Aid Societies across Ontario, Canada. Methods: Using cross tabulations with Fisher exact tests, the analysis draws on survey data from the second wave of the pandemic to test for significance of differences in areas of child safety reporting, interventions with newcomer families, and available supports across urban and urban/rural settings. Findings: Parents' emotional instability and substance use (86%), domestic/adult conflict (85.6%), and child emotional harm (66.3%) were the top child safety issues with most increased reporting during the pandemic. Except for domestic/adult conflict, there were no differences in the rating of the six identified areas of child abuse across newcomer/racialized caseloads in different geographical settings. Increasingly, during the COVID-19 pandemic, workers were intervening with newcomer families by ‘connecting them with community agencies or services’ (51.8%), and ‘reaching out to extended family and other community members to support parents’ (44.6%). Mental health supports (68.4%), family access (66.7%), and childcare (65.9%) were the least accessible services. Conclusion: A closer examination of the reported child safety incidents shows that child emotional harm was on the rise and that child sexual and physical abuse were underreported. Unidentified cases of child abuse during the pandemic posed barriers to help-seeking and resulted in limited or no supports for victims.